Investigation of acid-base equilibriums of some newly synthesized arylhydrazones of substituted benzhydrazides - Mirjana Jankulovska (My University, 2012)
A three series of p-substituted aromatic hydrazones have been synthesized by condensation of benzhydrazide/p-substituted benzhydrazides (CH3, OCH3, Cl and OH) with benzaldehyde/p-substituted benzaldehyde (OCH3 and NO2). Initially, p-substituted esters were prepared from benzoic acid, p-substituted benzoic acid and methanol. In the second step, p-substituted hydrazides were prepared from the previously synthesized esters and hydrazine hydrate. Finally, p-substituted aromatic hydrazones were obtained from hydrazides and benzaldehyde or p-substituted benzaldehyde. The identification of the synthesized hydrazones was confirmed by the following techniques: 1H NMR, 13C NMR, IR and UV-Vis spectroscopy and element analysis (CHN). Using the concept of linear salvation energy relationship (LFER) based on mono and the dual substituent parameters, quantitative assessment of the substituent effects on the substituent chemical shifts was made. The spectral behavior of some p-substituted aromatic hydrazones was examined by the UV-Vis spectroscopic technique in the pH region and the acid-base equilibriums was characterized qualitatively and quantitatively. The UV-Vis spectra of the solution at different pH were studied and the position of the absorption maximum was defined in neutral, acidic and basic media, and the electron transitions were discussed, too. It was confirmed that the protonation and dissociation processes take place in one step. The exceptions are hydrazones which contain phenolic group in theirs molecules. The changes in the UV-Vis spectra were utilized for determination of the concentration dissociation constants graphically and numerically. The pKBH+ and pKHA/pKH2A values were determined from the absorbance values of experimental and reconstructed spectra obtained by characteristic vector analysis (CVA). In order to obtain thermodynamic pKBH+ values measurements were performed at ionic strengths of 0.1 mol/dm3, 0.25 mol/dm3 and 0.5 mol/dm3. Furthermore, the influence of the substituents on the changes of the UV spectra, as well as, on the values of the dissociation constants was discussed. The site of protonation in the hydrazone molecule was determined using the values of proton affinity, while the site of the dissociation of the proton could be predicted using deprotonation enthalpy values. These parameters were found with the quantum-chemical calculations using AM1 and PM3 semiempirical methods. Also, the stability of the unprotonated and protonated isomers (E and Z) which exist in the solution was discussed.
Keywords: p-substituted aromatic hydrazones, synthesis, influence of substituents, NMR, IR, UV-Vis spectrophotometry, protonation, dissociation, concentration dissociation constants, thermodynamic dissociation constants, semiempirical methods (AM1 and PM3)